1998
DOI: 10.1111/j.1472-8206.1998.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan and dextrorphan in rats: Common antitussives — Different behavioural profiles

Abstract: Dextromethorphan (DM), a widely used and well-tolerated centrally acting antitussive, has been tested in several clinical trials for its antiepileptic and neuroprotective properties. However, the use of DM in these new clinical indications requires higher doses than antitussive doses, which may therefore induce phencyclidine (PCP)-like side-effects (memory and psychotomimetic disturbances) through its metabolic conversion to the active metabolite dextrorphan (DX), a more potent PCP-like non-competitive antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…Similarly, DM has been reported to impair spatial learning in the Morris water maze in a dose-dependent manner (31), consistent with the water-maze effects of other NMDA-receptor antagonists (e.g., MK-801 and AP-5) reported by other investigators (26). On the other hand, the memory impairment caused by DX is more pronounced than that of DM (32), and the prolonged use of DM produces cognitive deterioration in humans (33).…”
Section: Cognitive Dysfunctionsupporting
confidence: 78%
“…Similarly, DM has been reported to impair spatial learning in the Morris water maze in a dose-dependent manner (31), consistent with the water-maze effects of other NMDA-receptor antagonists (e.g., MK-801 and AP-5) reported by other investigators (26). On the other hand, the memory impairment caused by DX is more pronounced than that of DM (32), and the prolonged use of DM produces cognitive deterioration in humans (33).…”
Section: Cognitive Dysfunctionsupporting
confidence: 78%
“…14,83,84 Although difficult to extrapolate human dose requirements from animal data, it seems that DM doses higher than typically used for antitussive effects (60 -120 mg/d, oral), and those used in most previous neuroprotection trials, are required for neuroprotection. 68,81,85 However, in the trial with HD patients, plasma concentrations were undetectable in some patients after DM doses that were up to 8 times the maximum antitussive dose. 72 One method for increasing the central bioavailability of DM is to coadminister the specific and reversible CYP2D6 inhibitor, quinidine, to protect DM from extensive first-pass elimination via the cytochrome P4502D6 enzyme.…”
mentioning
confidence: 94%
“…Although this active metabolite is partially responsible for the neuroprotective effects in some models, 24,31,35 its action as a more potent phencyclidine (PCP)-like uncompetitive NMDA receptor antagonist is also associated with psychotomimetic disturbances. [85][86][87] Given the robust preclinical …”
mentioning
confidence: 99%
“…Furthermore, neither the discriminative stimulus (Gavend et al, 1995) nor the anticonvulsant (Kim et al, 2003) effects of dextromethorphan seem to result primarily from its metabolism to dextrorphan. Although some studies have found no difference between the jpet.aspetjournals.org behavioral syndromes produced by dextromethorphan and dextrorphan (Ishmael et al, 1998), others have found different behavioral profiles (Dematteis et al, 1998). The nature and the clinical relevance of the non-NMDA receptor-mediated effects of dextromethorphan are unknown.…”
Section: Discussionmentioning
confidence: 99%